Glycemic control among type 2 diabetes mellitus patients visiting the Emergency department of Gandaki Medical College: A cross-sectional study - Pokhrel, Shanti; Gautam, Bijaya (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Diabetes mellitus (DM) is a metabolic disorder which is characterized by increased blood glucose level. Glycated hemoglobin (HbA1c) is the most reliable indicator of long-term glycemic control as it accurately reflects an individual’s blood glucose levels during the preceding 2 to 3 months. Elevated level of HbA1c has been identified as a significant risk factor for other diseases such as cardiovascular diseases, stroke. This study aimed to evaluate the glycemic control in type 2 DM.Methods: After obtaining an ethical clearance, patients with Type 2 DM, confirmed according to American diabetes association criteria, who attended to the Gandaki Medical College Emergency Department were enrolled in this study.Results: Out of 117 patients, prevalence of poor glycemic control was 24.80% followed by inadequate control was 37.60% and fair control was 21.40%. HbA1c level did not show statistical significance with other risk factor.Conclusions: In this study, hypertension, COPD, hyperthyroidism and hypothyroidism were found as comorbidity in (53.0%) each of diabetes patients.